(untitled) (Medical Forum Monthly, 2023)
Objective: To assess the results of percutaneous coronary intervention (PCI) treatment in patients presenting late with acute anterior wall myocardial infarction (MI) complicated by complete heart block. Study Design: Descriptive cross-sectional Study. Place and Duration of Study: This study was conducted at the Cardiology Department of Lady Reading Hospital in Peshawar, Pakistan, between November 2018 and October 2021. Methods: In this study total 40 patients of acute anterior wall myocardial infarction (MI) with total heart block who presented with a delay of 24 hours or more were included. Each patient had a temporary pacemaker implanted before undergoing coronary angiography and attempting percutaneous coronary intervention (PCI) of the left anterior descending artery (LAD). Recovery time from heart block, need for permanent pacemaker implantation, and in-hospital mortality were included as outcome measures, coupled with restoration of normal sinus rhythm. The social science statistical tool SPSS Version 21.0 was used for the analysis and p-value ≤0.05 was considered as significant. Results: The study population had a mean age of 56.01 ± 6.91 years, with 67.5 % being male (n=27). Among the patients, 60 % had diabetes (n=24), 55 % had hypertension (n=22), 35 % were smokers (n=14), and 55 % had dyslipidemia (n=22). The average delay in presentation was 69.35 ± 11.13 hours. The mean time for restoring normal sinus rhythm was 68.11±11.12 hours, ranging from a minimum of 48 hours to a maximum of 86 hours. The mean troponin I level was 14.77 ± 89.6 pg/ml, and the mean ejection fraction was 43.6±8.27. Notably, 90% successful PCI showed a significant correlation with recovery time (p=0.004). Conclusion: The successful percutaneous coronary intervention (PCI) performed on the affected artery in patients with delayed presentation of complete heart block (CHB) and acute anterior myocardial infarction (MI).